Pengaruh Penggunaan Shopeepay Later Dan Mendapatkan Flash Sale Terhadap Impulse Buying Pada Pengguna Shopee Di Kota Medan - Fhadia Rizka Azhari; Erni Junaida; Rahmi Meutia (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
Shopee is a marketplace that sells various types of products by providing promotions in the form of flash sales or exclusive offers that can encourage impulse buying actions, shopee also offers payment features using shopeepay later which can affect consumer spending patterns so that impulse buying actions occur. This study aims to determine the effect of shopeepay later and flash sale on impulse buying on Shopee users in Medan. This study uses basic analysis methods using multiple linear regression, t test, F test, and coefficient of determination test (Adjusted R2). The results of this study indicate that the results of the variable t test shopeepay later (X1) and flash sale (X2) partially significantly affect impulse buying on Shopee users in Medan. The results of the F test showed that shopeepay later (X1) and flash sale (X2) simultaneously had a significant effect on impulse buying on Shopee users in Medan City.